Rubber plantations in tropical landscapes: agronomic systems, environmental impacts, and evidence-based management recommendations - Fadeila Mohammed Hashim Ali; Syaharudin bin Zaibon; Md Kamal Uddin; Ahmed Abubakar; Shamsul Haque (Universitas Sebelas Maret, 2025)
While Natural Rubber (NR) supports global supply chains, rapid expansion in South and Southeast Asia has noticeable effects on biodiversity, hydrology, and the carbon balance. This review synthesises the economic importance, environmental challenges, commercial applications, and ecological impacts of rubber production and plantation expansion. Furthermore, the study combines high-resolution deforestation attribution (Sentinel-2/Landsat), Eddy-Covariance (EC) comparisons of plantations and nearby tropical forests, and models that include a rubber-specific Plant Functional Type (PFT). In addition, conversion from forest to rubber consistently simplifies habitats, decreases species richness and functional diversity, reduces ecosystem carbon storage, raises peak flows and sediment export, and lowers baseflow. Conversely, replacing annual cropland can increase above-ground biomass and provide partial carbon gains. As such, results depend systematically on prior land use, monsoon intensity and rainfall patterns, elevation, and management practices (monoculture versus diversified agroforestry). The study recommends directing new planting onto already cleared land through spatial planning and reliable traceability; adopting diversified rubber agroforestry and soil- and water-conserving methods. This includes explicitly integrating rubber within zero-deforestation policies and results-based carbon payments. In line with this, rubber-specific modelling and open flux datasets should support climate-risk assessments and monitoring. Overall, focused governance and agroforestry strategies can balance ecological trade-offs while maintaining production, aligning natural-rubber supply with verifiable climate and biodiversity safeguards.